Nanofiller modified polycarbonate plastic and preparation method thereof
The nanofiller modified polycarbonate plastic addresses the limitations of existing nanofillers by combining carbon nanotubes, acrylic acid, vinyl triethoxysilane, and modified montmorillonite, achieving enhanced wear resistance, corrosion resistance, and high strength.
Patent Information
- Application Number
- CN202411324499.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-31
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing nanofillers for polycarbonate plastics fail to simultaneously achieve wear resistance, corrosion resistance, and high strength, limiting their application in demanding markets.
A nanofiller modified polycarbonate plastic is prepared by mixing a composite filler made of carbon nanotubes, acrylic acid, vinyl triethoxysilane, and sodium silicate, along with modified montmorillonite, through a series of chemical modifications and extrusion processes to enhance mechanical properties and resistance.
The modified nanofiller enhances wear resistance, corrosion resistance, and high strength, improving the overall performance of polycarbonate plastics.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plastic preparation, in particular to a nano-filler modified polycarbonate plastic and a preparation method thereof. Background Art
[0002] Polycarbonate is one of the five major engineering plastics, with excellent mechanical properties, electrical properties, dimensional stability, solvent resistance and other characteristics, and is widely used in automobile manufacturing, electronic appliances, medical equipment, aerospace and other fields. However, with the rapid development of science and technology, the application market has put forward higher performance requirements for PC products, and modifying PC is an effective way to meet this requirement.
[0003] When inorganic nanopowders are added to plastic polymers, they can be well combined with the plastic matrix due to their small size. When the plastic is subjected to external impact, the nanopowder can absorb the external impact energy and play a buffering role, so the nanopowder has a toughening effect on the plastic polymer. However, the existing nanofillers are too single and cannot achieve the effects of wear resistance, corrosion resistance and high strength at the same time, which limits the application of polycarbonate plastics. Summary of the invention
[0004] The purpose of the present invention is to provide a nanofiller modified polycarbonate plastic and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solution: a nanofiller modified polycarbonate plastic, wherein the nanofiller modified polycarbonate plastic is prepared by mixing modified nanofiller with polycarbonate.
[0006] Furthermore, the modified nanofiller includes a composite filler and modified montmorillonite.
[0007] Furthermore, the composite filler is made of carbon nanotubes, acrylic acid, vinyl triethoxysilane and sodium silicate.
[0008] Furthermore, the modified montmorillonite is prepared from sodium salt of N-ethyl-N-(2-hydroxy-3-sulfopropyl)-3-methylaniline, acrylamide and montmorillonite.
[0009] Furthermore, a method for preparing a nanofiller-modified polycarbonate plastic comprises the following preparation steps:
[0010] (1) placing 27 to 39 parts of carbon nanotubes in a container, adding 52 to 76 parts of 20 wt% sulfuric acid and 50 to 74 parts of 20 wt% nitric acid, ultrasonicating at 20 to 30° C. for 1 to 3 hours, heating to 100 to 120° C. for reaction for 1 to 2 hours, washing with 97 to 123 parts of deionized water for 3 times, and drying at 50 to 60° C. for 4 to 8 hours to obtain hydroxylated carbon nanotubes;
[0011] (2) 16 to 28 parts of hydroxylated carbon nanotubes, 3 to 5 parts of 4-dimethylaminopyridine, 30 to 54 parts of dicyclohexylcarbodiimide, and 108 to 214 parts of tetrahydrofuran are mixed uniformly, and 20 to 32 parts of acrylic acid are added at 50 to 60° C. under nitrogen protection. After reacting for 24 to 48 hours, the solid product is collected, washed three times with 57 to 89 parts of tetrahydrofuran, and dried at 60 to 80° C. for 6 to 10 hours to obtain modified carbon nanotubes;
[0012] (3) 15 to 27 parts of modified carbon nanotubes and 2 to 4 parts of ammonium persulfate solid are dispersed in 97 to 122 parts of ethanol at 20 to 30° C. and 50 kHz ultrasonic dispersion, 11 to 23 parts of vinyl triethoxysilane are added under nitrogen protection, the temperature is raised to 60 to 70° C. and the reaction is performed for 6 to 10 hours, the solid is collected, washed with 68 to 94 parts of ethanol for 3 times, and dried at 50 to 70° C. for 8 to 12 hours to obtain composite carbon nanotubes;
[0013] (4) adding 8 to 12 parts of composite carbon nanotubes to 84 to 128 parts of deionized water, stirring for 10 to 20 hours, adding 3 to 5 parts of saturated sodium silicate aqueous solution, 16 to 24 parts of ammonia water, and 65 to 77 parts of ethanol, stirring for 24 to 42 hours, filtering to obtain a filter cake, washing three times with 52 to 68 parts of deionized water, and drying at 50 to 70° C. for 5 to 7 hours to obtain a composite filler;
[0014] (5) 17 to 23 parts of sodium salt of N-ethyl-N-(2-hydroxy-3-sulfopropyl)-3-methylaniline and 25 to 33 parts of acrylamide are mixed evenly, 1 to 5 parts of potassium carbonate aqueous solution are added, reacted at 90 to 110° C. for 16 to 24 hours, extracted with ethyl acetate three times, and concentrated at a vacuum degree of -0.1 MPa to -0.06 MPa for 2 to 4 hours to obtain a modifier;
[0015] (6) adding 5 to 9 parts of montmorillonite to 178 to 320 parts of deionized water, stirring at 60 to 70° C. for 10 to 14 hours, adding 2 to 6 parts of a modifier, reacting at 70 to 90° C. for 8 to 10 hours, centrifuging at 1800 rpm / min for 10 minutes, washing three times with 87 to 101 parts of deionized water, and drying at 50 to 70° C. for 8 to 10 hours to obtain modified montmorillonite;
[0016] (7) grinding 19 to 27 parts of the composite filler and 24 to 36 parts of the modified montmorillonite in a high-speed ball mill for 3 to 9 minutes to obtain a modified nanofiller;
[0017] (8) Add 56-88 parts of modified nanofiller and 110-170 parts of polycarbonate into a mixer, add 8-12 parts of stabilizer and 2-4 parts of plasticizer and mix well, then put into a twin-screw compounding extruder at a head temperature of 175-185°C, a screw speed of 150-250 r / min, and an extrusion pressure of 4-12 MPa for extrusion, and pelletize to obtain nanofiller modified polycarbonate plastic.
[0018] Furthermore, the ultrasonic frequency in step (1) is 20 to 100 kHz.
[0019] Furthermore, the concentration of the potassium carbonate aqueous solution in step (5) is 0.1 mol / L.
[0020] Furthermore, the speed of the high-speed ball mill in step (7) is 800-1200 r / min.
[0021] Furthermore, the stabilizer in step (8) is one or more of sodium alginate, zinc stearate, and barium stearate.
[0022] Furthermore, the plasticizer in step (8) is one or more of dicyclohexyl phthalate, dibutyl phthalate and diethyl phthalate.
[0023] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0024] The invention oxidizes the carbon nanotubes under acidic conditions to make the surfaces of the carbon nanotubes have hydroxyl groups, and then polymerizes the carbon nanotubes with acrylic acid in situ to make the polyacrylic acid grafted on the surfaces of the carbon nanotubes, thereby improving the dispersibility of the carbon nanotubes, improving the flexibility of the materials, and enhancing the bearing capacity; then vinyl triethoxysilane participates in the polymerization reaction of acrylic acid to enhance the wear resistance, prevent the infiltration of chemical solutions, and improve the hydrophobic effect of the materials, while introducing silicon ethoxy groups to provide reaction points; then sodium silicate aqueous solution is added to make the carbon nanotubes grow in situ on the polymer surface to form stably combined and uniformly dispersed nano silicon dioxide, effectively reinforce the polycarbonate plastic, and improve the wear resistance and flexibility; on this basis, the nano filler is formed by mixing with modified montmorillonite through high-speed ball milling, and the nano filler is mixed with the polycarbonate plastic for modification to achieve the effects of wear resistance, corrosion resistance, and high strength.
[0025] The modified montmorillonite is prepared from sodium salt of N-ethyl-N-(2-hydroxy-3-sulfopropyl)-3-methylaniline, acrylamide and montmorillonite. The hydroxyl group of sodium salt of N-ethyl-N-(2-hydroxy-3-sulfopropyl)-3-methylaniline is reacted with the alkenyl group of acrylamide to introduce a benzene ring, thereby enhancing the mechanical strength of the plastic and improving the wear resistance. Meanwhile, the amide bond is provided to change the material from hydrophilic to hydrophobic, thereby isolating the corrosive liquid from entering and achieving a preliminary anti-corrosion effect. On this basis, the presence of the sulfonic acid radical makes it impossible for the plastic to undergo a replacement reaction with an acidic medium, thereby enhancing the anti-corrosion ability. The modified montmorillonite is then combined with the montmorillonite, and the organic group is covered on the surface of the montmorillonite or inserted between its layers through cation exchange, thereby increasing the interlayer distance, improving the dispersibility and stability of the montmorillonite and improving the compatibility with polycarbonate. DETAILED DESCRIPTION
[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0027] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the nanofiller-modified polycarbonate plastics prepared in the following examples are as follows:
[0028] Tensile strength: Take the same size of the embodiment and the comparative example to carry out the tensile strength test, and refer to GB / T13022-91 "Test method for tensile properties of plastic films" for testing.
[0029] Acid resistance: Take the embodiment and comparative example of the same size and put them into 1 mol / L hydrochloric acid solution and soak them for 100 hours. The grades are expressed as follows: Grade 0 - the mass change rate before and after corrosion is less than 0.001%; Grade 1 - the mass change rate before and after corrosion is greater than 0.001% and less than 0.010%; Grade 2 - the mass change rate before and after corrosion is greater than 0.010% and less than 0.030%; Grade 3 - the mass change rate before and after acid corrosion is greater than 0.030% and less than 0.050%; Grade 4 - the mass change rate before and after corrosion is greater than 0.050% and less than 0.10%.
[0030] Wear test: Take the embodiment and comparative example of the same size, and test the wear resistance of the plastic with reference to GB / T3960-2016 "Test Method for Sliding Friction and Wear of Plastics", and record the wear quality.
[0031] Example 1
[0032] (1) 27 parts of carbon nanotubes were placed in a container, 52 parts of 20 wt% sulfuric acid and 50 parts of 20 wt% nitric acid were added, ultrasonicated at 20°C and 20 kHz for 1 hour, heated to 100°C for reaction for 1 hour, washed 3 times with 97 parts of deionized water, and dried at 50°C for 4 hours to obtain hydroxylated carbon nanotubes;
[0033] (2) 16 parts of hydroxylated carbon nanotubes, 3 parts of 4-dimethylaminopyridine, 30 parts of dicyclohexylcarbodiimide, and 108 parts of tetrahydrofuran were mixed uniformly, and 20 parts of acrylic acid were added at 50° C. under nitrogen protection. After reacting for 24 hours, the solid product was collected, washed three times with 57 parts of tetrahydrofuran, and dried at 60° C. for 6 hours to obtain modified carbon nanotubes;
[0034] (3) 15 parts of modified carbon nanotubes and 2 parts of ammonium persulfate solid were ultrasonically dispersed in 97 parts of ethanol at 20°C and 50kHz, 11 parts of vinyltriethoxysilane were added under nitrogen protection, the temperature was raised to 60°C for reaction for 6 hours, the solid was collected, washed 3 times with 68 parts of ethanol, and dried at 50°C for 8 hours to obtain composite carbon nanotubes;
[0035] (4) adding 8 parts of composite carbon nanotubes to 84 parts of deionized water, stirring for 10 hours, adding 3 parts of saturated sodium silicate aqueous solution, 16 parts of ammonia water, and 65 parts of ethanol, stirring for 24 hours, filtering the filter cake, washing it three times with 52 parts of deionized water, and drying it at 50° C. for 5 hours to obtain a composite filler;
[0036] (5) 17 parts of sodium salt of N-ethyl-N-(2-hydroxy-3-sulfopropyl)-3-methylaniline and 25 parts of acrylamide were mixed evenly, 1 part of 0.1 mol / L potassium carbonate aqueous solution was added, reacted at 90° C. for 16 h, extracted with ethyl acetate 3 times, and concentrated at a vacuum degree of -0.1 MPa for 2 h to obtain a modifier;
[0037] (6) 5 parts of montmorillonite were added to 178 parts of deionized water, stirred at 60°C for 10 hours, 2 parts of a modifier were added, reacted at 70°C for 8 hours, centrifuged at 1800 rpm / min for 10 minutes, washed three times with 87 parts of deionized water, and dried at 50°C for 8 hours to obtain modified montmorillonite;
[0038] (7) placing 19 parts of the composite filler and 24 parts of the modified montmorillonite in a high-speed ball mill and grinding at 800 r / min for 3 min to obtain a modified nanofiller;
[0039] (8) 56 parts of modified nanofiller and 110 parts of polycarbonate were added into a mixer, 8 parts of sodium alginate and 2 parts of dicyclohexyl phthalate were added and mixed evenly, and then put into a twin-screw compounding extruder at a head temperature of 175° C., a screw speed of 150 r / min, and an extrusion pressure of 4 MPa for extrusion, and pelletized to obtain nanofiller modified polycarbonate plastic.
[0040] Example 2
[0041] (1) 33 parts of carbon nanotubes were placed in a container, 64 parts of 20 wt% sulfuric acid and 62 parts of 20 wt% nitric acid were added, ultrasonicated at 25°C and 60kHz for 2 hours, heated to 110°C for reaction for 1.5 hours, washed 3 times with 110 parts of deionized water, and dried at 55°C for 6 hours to obtain hydroxylated carbon nanotubes;
[0042] (2) 22 parts of hydroxylated carbon nanotubes, 4 parts of 4-dimethylaminopyridine, 42 parts of dicyclohexylcarbodiimide, and 161 parts of tetrahydrofuran were mixed uniformly, and 26 parts of acrylic acid were added at 55° C. under nitrogen protection. After reacting for 36 hours, the solid product was collected, washed three times with 73 parts of tetrahydrofuran, and dried at 70° C. for 8 hours to obtain modified carbon nanotubes;
[0043] (3) 21 parts of modified carbon nanotubes and 3 parts of ammonium persulfate solid were ultrasonically dispersed in 110 parts of ethanol at 25°C and 50kHz, 17 parts of vinyltriethoxysilane were added under nitrogen protection, the temperature was raised to 65°C for reaction for 8h, the solid was collected, washed 3 times with 81 parts of ethanol, and dried at 60°C for 10h to obtain composite carbon nanotubes;
[0044] (4) adding 10 parts of composite carbon nanotubes to 106 parts of deionized water, stirring for 15 hours, adding 4 parts of saturated sodium silicate aqueous solution, 20 parts of ammonia water, and 71 parts of ethanol, stirring for 33 hours, filtering the filter cake, washing it three times with 60 parts of deionized water, and drying it at 60° C. for 6 hours to obtain a composite filler;
[0045] (5) 20 parts of sodium salt of N-ethyl-N-(2-hydroxy-3-sulfopropyl)-3-methylaniline and 29 parts of acrylamide were mixed evenly, 3 parts of 0.1 mol / L potassium carbonate aqueous solution were added, reacted at 100° C. for 20 h, extracted with ethyl acetate 3 times, and concentrated at a vacuum degree of -0.08 MPa for 3 h to obtain a modifier;
[0046] (6) 7 parts of montmorillonite were added to 249 parts of deionized water, stirred at 65°C for 12 hours, 4 parts of a modifier were added, reacted at 80°C for 9 hours, centrifuged at 1800 rpm / min for 10 minutes, washed three times with 94 parts of deionized water, and dried at 60°C for 9 hours to obtain modified montmorillonite;
[0047] (7) placing 23 parts of the composite filler and 30 parts of the modified montmorillonite in a high-speed ball mill and grinding at 1000 r / min for 6 min to obtain a modified nanofiller;
[0048] (8) 77 parts of modified nanofiller and 140 parts of polycarbonate were added into a mixer, and 10 parts of zinc stearate and 3 parts of dibutyl phthalate were added and mixed evenly. The mixture was then put into a twin-screw compounding extruder and extruded at a head temperature of 180° C., a screw speed of 200 r / min, and an extrusion pressure of 8 MPa. The mixture was pelletized to obtain nanofiller modified polycarbonate plastic.
[0049] Example 3
[0050] (1) 39 parts of carbon nanotubes were placed in a container, 76 parts of 20 wt% sulfuric acid and 74 parts of 20 wt% nitric acid were added, ultrasonicated at 30°C and 100 kHz for 3 h, heated to 120°C for reaction for 1-2 h, washed 3 times with 123 parts of deionized water, and dried at 60°C for 8 h to obtain hydroxylated carbon nanotubes;
[0051] (2) 28 parts of hydroxylated carbon nanotubes, 5 parts of 4-dimethylaminopyridine, 54 parts of dicyclohexylcarbodiimide, and 214 parts of tetrahydrofuran were mixed uniformly, and 32 parts of acrylic acid were added at 60° C. under nitrogen protection. After reacting for 48 hours, the solid product was collected, washed three times with 89 parts of tetrahydrofuran, and dried at 80° C. for 10 hours to obtain modified carbon nanotubes;
[0052] (3) 27 parts of modified carbon nanotubes and 4 parts of ammonium persulfate solid were ultrasonically dispersed in 122 parts of ethanol at 30°C and 50kHz, 23 parts of vinyltriethoxysilane were added under nitrogen protection, the temperature was raised to 70°C for reaction for 10 hours, the solid was collected, washed three times with 94 parts of ethanol, and dried at 70°C for 12 hours to obtain composite carbon nanotubes;
[0053] (4) adding 12 parts of composite carbon nanotubes to 128 parts of deionized water, stirring for 20 hours, adding 5 parts of saturated sodium silicate aqueous solution, 24 parts of ammonia water, and 77 parts of ethanol, stirring for 42 hours, filtering the filter cake, washing it three times with 68 parts of deionized water, and drying it at 70° C. for 7 hours to obtain a composite filler;
[0054] (5) 23 parts of sodium salt of N-ethyl-N-(2-hydroxy-3-sulfopropyl)-3-methylaniline and 33 parts of acrylamide were mixed evenly, 5 parts of 0.1 mol / L potassium carbonate aqueous solution were added, reacted at 110° C. for 24 h, extracted with ethyl acetate 3 times, and concentrated at a vacuum degree of -0.06 MPa for 4 h to obtain a modifier;
[0055] (6) 9 parts of montmorillonite were added to 320 parts of deionized water, stirred at 70°C for 14 hours, 6 parts of a modifier were added, reacted at 90°C for 10 hours, centrifuged at 1800 rpm / min for 10 minutes, washed three times with 101 parts of deionized water, and dried at 70°C for 10 hours to obtain modified montmorillonite;
[0056] (7) placing 27 parts of the composite filler and 36 parts of the modified montmorillonite in a high-speed ball mill and grinding at 1200 r / min for 9 min to obtain a modified nanofiller;
[0057] (8) 88 parts of modified nanofiller and 170 parts of polycarbonate were added into a mixer, and 12 parts of barium stearate and 4 parts of diethyl phthalate were added and mixed evenly. The mixture was then put into a twin-screw compounding extruder and extruded at a head temperature of 185° C., a screw speed of 250 r / min, and an extrusion pressure of 12 MPa. The mixture was pelletized to obtain modified polycarbonate plastic.
[0058] Comparative Example 1
[0059] The difference between Comparative Example 1 and Example 2 is that there is no step (1) (2), and step (3) is changed to: 21 parts of acrylic acid and 3 parts of ammonium persulfate solid are ultrasonically dispersed in 110 parts of ethanol at 25°C and 50kHz, 17 parts of vinyl triethoxysilane are added under nitrogen protection, the temperature is raised to 65°C for reaction for 8h, the solid is collected, washed 3 times with 81 parts of ethanol, and dried at 60°C for 10h to obtain a composite polymer; step (4) is changed to: 10 parts of the composite polymer are added to 106 parts of deionized water, stirred for 15h, 4 parts of saturated sodium silicate aqueous solution, 20 parts of ammonia water, and 71 parts of ethanol are added and stirred for 33h, the filter cake is filtered, washed 3 times with 60 parts of deionized water, and dried at 60°C for 6h to obtain a composite filler. The remaining steps are the same as those in Example 2.
[0060] Comparative Example 2
[0061] The difference between Comparative Example 2 and Example 2 is that there is no step (2), and step (3) is changed to: 21 parts of hydroxylated carbon nanotubes and 3 parts of ammonium persulfate solid are ultrasonically dispersed in 110 parts of ethanol at 25°C and 50kHz, 17 parts of vinyltriethoxysilane are added under nitrogen protection, the temperature is raised to 65°C for reaction for 8h, the solid is collected, washed 3 times with 81 parts of ethanol, and dried at 60°C for 10h to obtain composite carbon nanotubes. The remaining steps are the same as those in Example 2.
[0062] Comparative Example 3
[0063] The difference between Comparative Example 3 and Example 2 is that step (3) is different. Step (3) is changed to: 21 parts of modified carbon nanotubes and 3 parts of ammonium persulfate solid are ultrasonically dispersed in 110 parts of ethanol at 25°C and 50kHz, the temperature is raised to 65°C for reaction for 8h, the solid is collected, washed 3 times with 81 parts of ethanol, and dried at 60°C for 10h to obtain composite carbon nanotubes. The remaining steps are the same as those in Example 2.
[0064] Comparative Example 4
[0065] The difference between Comparative Example 4 and Example 2 is that step (4) is omitted and step (7) is changed to: 23 parts of composite carbon nanotubes and 30 parts of modified montmorillonite are placed in a high-speed ball mill and ground at 1000 r / min for 6 minutes to obtain a modified nanofiller. The remaining steps are the same as those in Example 2.
[0066] Comparative Example 5
[0067] The difference between Comparative Example 5 and Example 2 is that there is no step (5), and step (6) is changed to: 7 parts of montmorillonite are added to 249 parts of deionized water, stirred at 65°C for 12 hours, 4 parts of acrylamide are added, reacted at 80°C for 9 hours, centrifuged at 1800 rpm / min for 10 minutes, washed 3 times with 94 parts of deionized water, and dried at 60°C for 9 hours to obtain modified montmorillonite. The remaining steps are the same as those in Example 2.
[0068] Comparative Example 6
[0069] The difference between Comparative Example 6 and Example 2 is that there is no step (5), and step (6) is changed to: 7 parts of montmorillonite are added to 249 parts of deionized water, stirred at 65° C. for 12 hours, 4 parts of N-ethyl-N-(2-hydroxy-3-sulfopropyl)-3-methylaniline sodium salt are added, reacted at 80° C. for 9 hours, centrifuged at 1800 rpm / min for 10 minutes, washed 3 times with 94 parts of deionized water, and dried at 60° C. for 9 hours to obtain modified montmorillonite. The remaining steps are the same as those in Example 2.
[0070] Comparative Example 7
[0071] The difference between Comparative Example 7 and Example 2 is that there is no step (6), and step (7) is changed to: 23 parts of the composite filler and 30 parts of the modifier are placed in a high-speed ball mill and ground at 1000 r / min for 6 minutes to obtain a modified nanofiller. The remaining steps are the same as in Example 2.
[0072] Effect example
[0073] Table 1 below shows the performance analysis results of polycarbonate plastics modified with nanofillers of Examples 1 to 3 of the present invention and Comparative Examples 1 to 7.
[0074] Tensile strength / MPa Acid resistance / grade Abrasion test / g Example 1 23.2 0 5.1 Example 2 23.6 0 4.7 Example 3 22.9 0 5.0 Comparative Example 1 13.7 3 8.2 Comparative Example 2 14.5 3 7.7 Comparative Example 3 12.8 4 11.9 Comparative Example 4 15.1 2 11.4 Comparative Example 5 14.3 4 10.3 Comparative Example 6 16.1 4 8.6 Comparative Example 7 16.4 2 9.5
[0075] From the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 1, it can be found that the introduction of carbon nanotubes can significantly improve the tensile strength of plastics and enhance the mechanical properties; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 2, it can be found that the dispersion of carbon nanotubes can be improved, the flexibility of the material can be improved, and the bearing capacity can be enhanced by in-situ polymerization of acrylic acid on the surface of carbon nanotubes; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 3, it can be found that the addition of vinyl triethoxy silane to participate in the polymerization can enhance the wear resistance, prevent the infiltration of chemical solutions, and improve the hydrophobic effect of the material. At the same time, the introduction of silicon ethoxy groups provides a growth site for silicon dioxide and reinforces the plastic again; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 4, it can be found that the sodium silicate aqueous solution can grow in-situ on the polymer surface to form stably combined and uniformly dispersed nano-silicon dioxide, effectively reinforce the polycarbonate plastic, and improve the wear resistance and tensile strength; from the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 5, it can be found that the addition of vinyl triethoxy silane to participate in the polymerization can enhance the wear resistance, prevent the infiltration of chemical solutions, and improve the hydrophobic effect of the material. At the same time, the introduction of silicon ethoxy groups provides a growth site for silicon dioxide and reinforces the plastic again. Data comparison shows that the benzene ring in sodium salt of N-ethyl-N-(2-hydroxy-3-sulfopropyl)-3-methylaniline can enhance the mechanical strength of plastics and improve wear resistance, and the presence of sulfonate makes it impossible for plastics to undergo replacement reaction with acidic media, thereby enhancing corrosion resistance. At the same time, metal cations are carried out to exchange cations with montmorillonite, so that organic groups are covered on the surface of montmorillonite or inserted between its layers, thereby increasing the interlayer spacing, improving the dispersibility and stability of montmorillonite, improving the compatibility with polycarbonate, and enhancing the performance of plastics. Comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 6 shows that the introduction of amide bonds by acrylamide can convert hydrophilic materials into hydrophobic materials, isolate corrosive liquids from entering, and achieve corrosion resistance. Comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 7 shows that the intercalation of the modifier between montmorillonite layers by ion exchange can improve the compatibility between the nanofiller and the plastic, thereby effectively enhancing the tensile strength and wear resistance of the plastic.
[0076] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A nanofiller modified polycarbonate plastic, characterized in that: The nano-filler modified polycarbonate plastic is prepared by mixing modified nano-filler with polycarbonate.
2. A nanofiller modified polycarbonate plastic according to claim 1, characterized in that: The modified nano filler includes a composite filler and modified montmorillonite.
3. A nanofiller modified polycarbonate plastic according to claim 2, characterized in that: The composite filler is prepared from carbon nanotubes, acrylic acid, vinyl triethoxysilane and sodium silicate.
4. The nanofiller modified polycarbonate plastic according to claim 2, characterized in that: The modified montmorillonite is prepared from sodium salt of N-ethyl-N-(2-hydroxy-3-sulfopropyl)-3-methylaniline, acrylamide and montmorillonite.
5. A method for preparing a nanofiller modified polycarbonate plastic, characterized in that: The method comprises the following preparation steps: (1) placing 27 to 39 parts of carbon nanotubes in a container, adding 52 to 76 parts of 20 wt% sulfuric acid and 50 to 74 parts of 20 wt% nitric acid, ultrasonicating at 20 to 30° C. for 1 to 3 hours, heating to 100 to 120° C. for reaction for 1 to 2 hours, washing with 97 to 123 parts of deionized water for 3 times, and drying at 50 to 60° C. for 4 to 8 hours to obtain hydroxylated carbon nanotubes; (2) 16 to 28 parts of hydroxylated carbon nanotubes, 3 to 5 parts of 4-dimethylaminopyridine, 30 to 54 parts of dicyclohexylcarbodiimide, and 108 to 214 parts of tetrahydrofuran are mixed uniformly, and 20 to 32 parts of acrylic acid are added at 50 to 60° C. under nitrogen protection. After reacting for 24 to 48 hours, the solid product is collected, washed three times with 57 to 89 parts of tetrahydrofuran, and dried at 60 to 80° C. for 6 to 10 hours to obtain modified carbon nanotubes; (3) 15 to 27 parts of modified carbon nanotubes and 2 to 4 parts of ammonium persulfate solid are dispersed in 97 to 122 parts of ethanol at 20 to 30° C. and 50 kHz ultrasonic dispersion, 11 to 23 parts of vinyl triethoxysilane are added under nitrogen protection, the temperature is raised to 60 to 70° C. and the reaction is performed for 6 to 10 hours, the solid is collected, washed with 68 to 94 parts of ethanol for 3 times, and dried at 50 to 70° C. for 8 to 12 hours to obtain composite carbon nanotubes; (4) adding 8 to 12 parts of composite carbon nanotubes to 84 to 128 parts of deionized water, stirring for 10 to 20 hours, adding 3 to 5 parts of saturated sodium silicate aqueous solution, 16 to 24 parts of ammonia water, and 65 to 77 parts of ethanol, stirring for 24 to 42 hours, filtering to obtain a filter cake, washing three times with 52 to 68 parts of deionized water, and drying at 50 to 70° C. for 5 to 7 hours to obtain a composite filler; (5) 17 to 23 parts of sodium salt of N-ethyl-N-(2-hydroxy-3-sulfopropyl)-3-methylaniline and 25 to 33 parts of acrylamide are mixed evenly, 1 to 5 parts of potassium carbonate aqueous solution are added, reacted at 90 to 110° C. for 16 to 24 hours, extracted with ethyl acetate three times, and concentrated at a vacuum degree of -0.1 MPa to -0.06 MPa for 2 to 4 hours to obtain a modifier; (6) adding 5 to 9 parts of montmorillonite to 178 to 320 parts of deionized water, stirring at 60 to 70° C. for 10 to 14 hours, adding 2 to 6 parts of a modifier, reacting at 70 to 90° C. for 8 to 10 hours, centrifuging at 1800 rpm / min for 10 minutes, washing three times with 87 to 101 parts of deionized water, and drying at 50 to 70° C. for 8 to 10 hours to obtain modified montmorillonite; (7) grinding 19 to 27 parts of the composite filler and 24 to 36 parts of the modified montmorillonite in a high-speed ball mill for 3 to 9 minutes to obtain a modified nanofiller; (8) Add 56-88 parts of modified nanofiller and 110-170 parts of polycarbonate into a mixer, add 8-12 parts of stabilizer and 2-4 parts of plasticizer and mix well, then put into a twin-screw compounding extruder at a head temperature of 175-185°C, a screw speed of 150-250 r / min, and an extrusion pressure of 4-12 MPa for extrusion, and pelletize to obtain nanofiller modified polycarbonate plastic.
6. The method for preparing a nanofiller modified polycarbonate plastic according to claim 6, characterized in that: The ultrasonic frequency in step (1) is 20 to 100 kHz.
7. The method for preparing a nanofiller modified polycarbonate plastic according to claim 6, characterized in that: The concentration of the potassium carbonate aqueous solution in step (5) is 0.1 mol / L.
8. The method for preparing a nanofiller modified polycarbonate plastic according to claim 6, characterized in that: The speed of the high-speed ball mill in step (7) is 800-1200 r / min.
9. The method for preparing a nanofiller modified polycarbonate plastic according to claim 6, characterized in that: The stabilizer in step (8) is one or more of sodium alginate, zinc stearate, and barium stearate.
10. The method for preparing a nanofiller modified polycarbonate plastic according to claim 6, characterized in that: The plasticizer in step (8) is one or more of dicyclohexyl phthalate, dibutyl phthalate and diethyl phthalate.
Citation Information
Patent Citations
High-strength wear-resistant engineering plastic and preparation method thereof
CN107987505A
Graphene-reinforced polycarbonate heat-conducting composite material and preparation method thereof
CN111117199A
Preparation process of high-strength wear-resistant modified plastic particles
CN115322399A
Modified PC plastic and preparation process thereof
CN117887238A
